Project Based Learning on Casting of Aluminium Tensile Test Specimen for Mechanical Engineering Students, State Polytechnic of Malang on Odd Semester of Academic Year 2016/2017 - Hadi, S.; Agustriyana, L.; Subagiyo, Subagiyo (Journal of Education Reseach and Evaluation, 2017)
The problem faced by students is the difficulty of understanding on metal casting topic in the lesson of Materials Technology which is conducted by lectures only. The research objective is to find out the improvement of score on metal casting topic for 1G students from Mechanical Engineering Department, State Polytechnic of Malang (Polinema) in odd Semester, Academic Year 2016/2017. Research method were facilitation of applied metal casting through pretest of metal casting, added a description of the design and modification of metal mould for Aluminium, visit to a home industry of Aluminium casting, students practice of Aluminium casting in a home industry, student groups presentation and discussion in the subtopics of (1) design and mould manufacture, (2) Aluminium casting practice, and (3) tensile testing with cast Aluminium specimen, as well as posttest on metal casting. The research result is an increasing in average score from 46.56 to 53.6 (22%) that means by adding the practice to the theory involved is increase a significant impact on understanding of Aluminium casting for students.